Implementasi Model Intervensi Keperawatan Berbasis Kader Posyandu untuk Pencegahan Stunting - Eka Rita Lestari; Ulfah Agus Sukrillah; Siti Mulidah (JURNAL KEPERAWATAN MERSI, 2026)
Background: Stunting remains a major public health problem in Indonesia, primarily caused by chronic malnutrition during the first 1,000 days of life. Posyandu cadres play a crucial role in early detection and prevention; however, their capacity in implementing community-based nursing interventions is still limited. Objective: This study aimed to analyze the effectiveness of a Posyandu cadre-based nursing intervention model in improving cadre knowledge, skills, and preventing stunting among toddlers in Banyumas Regency. Methods: This study employed a quasi-experimental randomized controlled trial with a pretest–posttest control group design. A total of 60 Posyandu cadres were selected through simple random sampling and divided into intervention and control groups. The intervention group received an eight-week training program, while the control group received standard education. Data were collected using knowledge questionnaires, skills observation sheets, and toddler nutritional status indicators, and analyzed using paired and independent t-tests. Results: The results showed a significant increase in knowledge (56.3 to 82.7; p<0.001) and skills (54.2 to 80.5; p<0.001) among cadres in the intervention group, while no significant changes were observed in the control group. Additionally, there was a 12% reduction in the proportion of toddlers at risk of stunting in the intervention group. Conclusion: The Posyandu cadre-based nursing intervention model effectively improves cadre capacity and contributes to stunting prevention, particularly in community and rural health settings.